Hybrid Contracts in Leasing and Ijarah Muntahiya Bit Tamlik in Indonesia Sharia Financial Institutions - Darti Busni; Doli Witro; Raid Alghani; Iwan Setiawan; Nana Herdiana Abdurrahman (EkBis: Jurnal Ekonomi dan Bisnis, 2022)
This article discusses the implementation of the concept of hybrid contracts in the product of ijarah al muntahiya bit tamlik (IMBT) and leasing at Indonesia Islamic Financial Institutions. This article aimed to find out the implementation of hybrid contract concept in IMBT and leasing products at Indonesia Islamic Financial Institutions. This article was conducted using qualitative research method. The data in this study were obtained from library materials such as books, journals, articles, etc. Data analysis techniques used were data condensation, data presentation, and drawing conclusions. The analysis results showed that the development of contracts in Islamic financial institutions was inevitable due to the implementation of multi-contracts. The merging of two contracts is also known as (hybrid contract or al-'uqudal-murakkabah) such as ijarah al mutahiya bit tamlik (IMBT). IMBT is a combination of two inter-ijarah contracts (lease) and the sale and purchase or grant is made at the end of the lease term. The implementation and merging of two contracts (hybrid contracts) in IMBT may use several contracts, including ijarah contract, ba'i contract, wakalah contract, and hibah contract.